Carrier dynamics in Landau-quantized graphene featuring strong Auger scattering - Mittendorff, Martin; Wendler, Florian; Malic, Ermin; Knorr, Andreas; Orlita, Milan; Potemski, Marek; Berger, Claire; de Heer, Walter A.; Schneider, Harald; Helm, Manfred; Winnerl, Stephan (Nature physics, 2015)
The energy spectrum of common two-dimensional electron gases consists of a harmonic (that is, equidistant) ladder of Landau levels, thus preventing the possibility of optically addressing individual transitions. In graphene, however, owing to its non-harmonic spectrum, individual levels can be addressed selectively. Here, we report a time-resolved experiment directly pumping discrete Landau levels in graphene. Energetically degenerate Landau-level transitions from n = −1 to n = 0 and from n = 0 to n = 1 are distinguished by applying circularly polarized THz light. An analysis based on a microscopic theory shows that the zeroth Landau level is actually depleted by strong Auger scattering, even though it is optically pumped at the same time. The surprisingly strong electron–electron interaction responsible for this effect is directly evidenced through a sign reversal of the pump–probe signal. Landau levels in graphene are not equidistant so that transitions between them can be individually probed. Time-resolved optical pumping experiments reveal strong electron–electron scattering resulting in an Auger-depleted zeroth order Landau level.